ANALISIS LITERATUR KEPEMIMPINAN TRANSFORMASIONAL DALAM KONTEKS ORGANISASI KESEHATAN - Oryza Sativa H Sihotang; Khairizah Afifah; Wasiyem Wasiyem; Fadlan Alhafizh Marpaung; Yuskaini Hadijah Rambe (STKIP PGRI Situbondo, 2025)
Kepemimpinan, atau